Antioxidant Activities of Various Brown Seaweeds from Seribu Islands - Seftylia Diachanty; N. Nurjanah; Asadatun Abdullah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Brown seaweeds contain various metabolites (carotenoids, laminarin, alginate, fucoidan, mannitol, and phlorotannin) as anticancer substances, antioxidants and chemopreventive agent against degenerative diseases. This research was aimed to determine the chemical properties and antioxidants activity of Sargassum polycystum, Padina minor and Turbinaria conoides. This research consisted of the proximate analysis, crude fiber, minerals, heavy metals, extraction, phytochemicals, analysis phenolic compound and antioxidant activity with DPPH, FRAP and CUPRAC methods. The results showed moisture content of S. polycystum, P.  minor, and T. conoides 24-31%, fat 0.23-0,47%, protein 3-4%, ash 27-45%, carbohydrate 26-38% and crude fiber 2-6%. Mineral Fe S. polycystum, P.minor and T.conoides about 0.03 g/kg to 0.39 g/kg, Ca 11.28 g/kg to 27.98 g/kg, K 13.86 g/kg to 41.15 g/kg, Na 16.31 g/kg to 20.51 g/kg and Mg 8.04 g/ kg to 18.68 g/kg. The range of heavy metals Pb S. polycystum, P.  m i n o r  and T. conoides 3.48 mg/kg to 12.68 mg/kg, Hg 0.24 mg/kg to 0.53 mg/kg and Cu 5.66 mg/kg to 7.02 mg/kg. Ethanol extract of S. polycystum, P. minor, and T. conoides contains alkaloids, phenolic, flavonoids, saponins, steroids, and triterpenoids. Total phenolic compounds of brown seaweeds ranged from 3758.97-8287.18 mg GAE/g. Brown seaweeds contain DPPH antioxidant activities within IC50 values of 1.9-9.6 mg/mL, FRAP 70.643-105.357 µmol Trolox/g and CUPRAC 85.268-201 µmol Trolox/g.